2021
DOI: 10.3390/su13095294
|View full text |Cite
|
Sign up to set email alerts
|

Food Security and COVID-19: A Systematic Review of the First-Year Experience

Abstract: For decades, global food security has not been able to address the structural problem of economic access to food, resulting in a recent increase in the number of undernourished people from 2014. In addition, the FAO estimates that the number of undernourished people drastically increased by 82–132 million people in 2020 due to the COVID-19 pandemic. To alleviate this dramatic growth in food insecurity, it is necessary to understand the nature of the increase in the number of malnourished during the pandemic. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 63 publications
1
21
0
5
Order By: Relevance
“…Unrelated to our study data, low income has been identified as the factor that most negatively affected food security during the ongoing COVID-19 pandemic [ 69 ]. As a consequence, food security remains a current topic in the United States, and the COVID-19 pandemic (and its imposed social isolation) exacerbated persistent sociopolitical barriers to food security [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unrelated to our study data, low income has been identified as the factor that most negatively affected food security during the ongoing COVID-19 pandemic [ 69 ]. As a consequence, food security remains a current topic in the United States, and the COVID-19 pandemic (and its imposed social isolation) exacerbated persistent sociopolitical barriers to food security [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…A substantial gap can be seen between the demand and supply of seafood in the near future with the current state of wild-capture fisheries and aquaculture [2]. The COVID-19 pandemic has increased threats to the global food system and further demonstrates the importance of resilient and sustainable animal-protein production systems [3,4]. This shows an urgent need for a new method for seafood production to build a productive, flexible, and resilient enterprise of current and future challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Con el estado actual de las producciones de pescados y mariscos provenientes de la acuicultura y pesca de captura salvaje, va a haber una gran diferencia entre la oferta y la demanda de pescados y mariscos en un futuro próximo (Banco Mundial 2014). Además, la pandemia de COVID-19 mostró las amenazas a la seguridad del sistema alimentario de Estados Unidos y del mundo, así como la importancia de contar con sistemas de producción de proteínas animales duraderas y resistentes (Éliás et al 2021;Mardones et al 2020). Esto demuestra la necesidad urgente de un método totalmente nuevo para la producir pescados y mariscos, con el fin de construir una empresa resistente, productiva y flexible frente a los desafíos actuales y futuros.…”
Section: Introductionunclassified